The Influence of Social Media on Consumer Choices: A Practical Investigation (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
This research examines the ways in which social media, with its interactive nature and ability to share content, shape consumer behavior in Baghdad. The study examines a range of social, psychological, and cultural factors that influence purchasing decisions in this context. We collected information by answering a questionnaire, a random sample of 140 social media users in Baghdad Governorate, and analyzed it using the statistical program SPSS. The results reveal that social media has a significant impact on consumer behavior, with 70% of respondents indicating that they purchased products based on recommendations they encountered on these platforms. This confirms the role of social media as a powerful channel for word-of-mouth marketing. The study concludes by providing recommendations for both consumers and businesses on how to effectively leverage these platforms.